Spatial Distribution and Influencing Factors of Agricultural Enterprise Brands in Guangxi - Shasha Ouyang; Jun Wen; Xingpeng Xu (Agriculture)
This study leverages advanced analytical tools such as ArcGIS spatial analysis and Geographical Detectors to conduct a comprehensive analysis of the spatial distribution characteristics, equilibrium, hotspot areas, and geographic associations of 164 district-level agribusiness brands in Guangxi, highlighting the unique insights these tools provide into the spatial heterogeneity of agricultural enterprise brands. Our findings reveal a significant concentration of brands in the northern region, particularly in Nanning, Liuzhou, and Guilin, with a dense northeast and sparse southwest distribution pattern. We identify a positive correlation between the number of regional brands and GDP and a negative correlation with distance from major highways. This suggests that regional economic development and transportation infrastructure significantly impact brand distribution. To enhance brand development, we recommend focusing on regional brand cultivation, innovation, and leveraging digital marketing strategies. This study provides actionable insights for policymakers and practitioners aiming to promote agricultural brand growth and rural revitalization in Guangxi. This pattern suggests that regions with abundant natural resources and higher economic development levels are more conducive to the formation and growth of agricultural enterprise brands, highlighting the importance of regional economic foundations and resource endowments in agricultural branding. Specifically, brands are primarily concentrated in the northern region, with Nanning, Liuzhou, and Guilin having a particularly high number of such brands. This pattern aligns with the core–periphery theory in economic geography, which suggests that economic activities tend to cluster around central cities due to agglomeration economies. The findings challenge the assumption that agricultural brands are evenly distributed across regions, highlighting the importance of regional economic foundations and infrastructure in brand development. Additionally, the significant positive correlation between the number of regional brands and Gross Domestic Product supports the idea that economic strength fosters brand development. Conversely, the significant negative correlation between the number of agricultural brand enterprises and the distance from major highways underscores the critical role of transportation infrastructure in facilitating market access and brand growth. Therefore, this study highlights the importance of cultivating regional brands, enhancing innovation capabilities, and advancing new marketing methods to promote the spatial equilibrium and sustainable development of agricultural enterprise brands, contributing to rural revitalization in Guangxi.